The Effect of Endorphin Massage on Reducing The Intensity of Back Pain in Third Trimester Pregnant Women: A Systematic Review - Astuti, Kh Endah Widhi; Murwati, Murwati; Fitriani, Nur (Journal of Maternal and Child Health, 2022)
Background: During the period of pregnancy, the mother will experience physical and psychological changes that will cause discomfort, one of them is back pain. Persistent pain not resolved immediately can result in chronic pain. Endorphin massage is a non-pharmacological method with touch or light massage techniques that can provide a feeling of calm and comfort to pregnant women who are entering late pregnancy until before labor. This study aimed to determine the effect of endorphin massage on decreasing back pain intensity in third trimester pregnant women. Subjects and Method: This systematic review uses three databased article searches, namely Pubmed, Research Gate and Schoolar with a publication time of the last 5 years. The criteria inclusion were pregnant women who experienced back pain and given endorphin massage. There was no comparison, quasi-experimental research design, randomized control and trial, qualitative research, cross-sectional. Articles published in 2015 – 2020 both of Indonesian and English Article.  The exclusion criteria were the article with systematic review method. Results: Nine articles that met the inclusion criteria were used in this study. The article mostly discusses the effect of endorphin massage on reducing back pain intensity in third trimester pregnant women (7 articles) and compares the effect of endorphin massage with other non-pharmacological therapies (2 articles) with 5 articles using a pre-experimental research design and 4 articles using a research design. Quasy-experiments and the average number of samples in the articles reviewed were more than 250 subjects. Conclusion: Endorphin massage is effective in reducing the intensity of back pain in the third trimester of pregnant women.